FVIII Immunogenicity—Bioinformatic Approaches to Evaluate Inhibitor Risk in Non-severe Hemophilia A - Hart, Daniel P. (Frontiers in Immunology, 2020)
The life-long inhibitor risk in non-severe haemophilia A has been an important clinical and research focus in recent years. Non-severe haemophilia A is most commonly caused by point mutation, missense F8 genotypes, of which over 800 variants are described. The immunogenic potential of just a single amino acid change within a complex 2332 amino acid protein is an important reminder of the challenges of protein replacement therapies in diverse, global populations. Bioinformatic approaches offer a strategy to dissect the contribution of F8 genotype in the context of the wider HLA diversity through which antigenic peptides will necessarily be presented. For the majority of F8 genotypes it is evident that inhibitor risk prediction is dependent on the combination of F8 genotype and available HLA II. In silico predictions still over call the risk of inhibitor occurrence suggestive of additional, generalisable mechanisms of “protection” against clinically meaningful inhibitor events. The structural homology between FVIII and FV provides an attractive mechanism by which some F8 genotypes may be afforded co-incidental tolerance through homology of FV and FVIII primary amino sequence. In silico strategies enable the extension of this hypothesis to analyse the extent to which co-incidental cross-matching exists between FVIII-derived primary peptide sequences and any other human proteome protein. This review of complimentary in vitro, in silico and clinical epidemiology data documents incremental insights into immunological mechanism of inhibitor occurrence in non-severe haemophilia A over the last decade. Complex questions remain about antigenic presentation to understand and predict individualised risk of inhibitor occurrence.